PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK KAHF DI KOTA BEKASI - Ridwan Fadhilah; Dewi Sri Woelandari; Ferawaty Puspitorini; Agus Dharmanto; Milda Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of product quality, brand image, and digital marketing on the purchase decision of Kahf products in Bekasi. In the modern era, where the body care and cosmetics industry is growing rapidly, consumers' understanding of the factors that influence purchasing decisions is crucial. The research method used is a survey with a quantitative approach, where data is collected through questionnaires distributed to consumers of Kahf products using an accidental sampling technique with the lemeshow formula. The population in this study is consumers who have bought or are potential buyers of Kahf products. The total sample used in this study was 100 respondents. In conducting tests using SPSS software version 26. Based on the results of the study, the variables of product quality, brand image, and digital marketing have a positive and significant effect on the decision to purchase kahf products in the city of Bekasi.